Territorial polarisation of the economy and population distribution in post-Soviet Russia - Fedorov Gennady (Bulletin of Geography. Socio-Economic Series)
Scientists, experts, and politicians have differing views on polarisation and levelling in the development of regions. Many researchers consider polarisation to be an objective process that benefits the country and the region because labour productivity is higher in larger centres. As for social differences, many states (and the European Union as an organisation) redistribute part of their revenue from more prosperous regions to poorer ones using regional budget policies. The article provides useful data on the regional specificity of polarisation and levelling in Russia at macro-, meso-, and microregional levels based on statistical, economic and cartographic analysis. The article shows that in Russia the polarisation of the economy and population distribution strongly prevails over the levelling of regional differences.